Augmentation therapies for treatment-resistant depression: systematic review and meta-analysis. (20th November 2018) - Strawbridge, Rebecca; Carter, Ben; Marwood, Lindsey; Bandelow, Borwin; Tsapekos, Dimosthenis; Nikolova, Viktoriya L.; Taylor, Rachael; Mantingh, Tim; de Angel, Valeria; Patrick, Fiona; Cleare, Anthony J.; Young, Allan H.
Abstract : Background: Depression is considered to have the highest disability burden of all conditions. Although treatment-resistant depression (TRD) is a key contributor to that burden, there is little understanding of the best treatment approaches for it and specifically the effectiveness of available augmentation approaches. Aims: We conducted a systematic review and meta-analysis to search and quantify the evidence of psychological and pharmacological augmentation interventions for TRD. Method: Participants with TRD (defined as insufficient response to at least two antidepressants) were randomised to at least one augmentation treatment in the trial. Pre-post analysis assessed treatment effectiveness, providing an effect size (ES) independent of comparator interventions. Results: Of 28 trials, 3 investigated psychological treatments and 25 examined pharmacological interventions. Pre-post analyses demonstrated N -methyl-d -aspartate-targeting drugs to have the highest ES (ES = 1.48, 95% CI 1.25–1.71). Other than aripiprazole (four studies, ES = 1.33, 95% CI 1.23–1.44) and lithium (three studies, ES = 1.00, 95% CI 0.81–1.20), treatments were each investigated in less than three studies. Overall, pharmacological (ES = 1.19, 95% CI 1.80–1.30) and psychological (ES = 1.43, 95% CI 0.50–2.36) therapies yielded higher ESs than pill placebo (ES = 0.78, 95% CI 0.66–0.91) and psychological control (ES = 0.94, 95% CI 0.36–1.52). Conclusions: Despite being used widely in clinical practice, the evidence for augmentation treatments in TRD is sparse. Although pre-post meta-analyses are limited by the absence of direct comparison, this work finds promising evidence across treatment modalities. Declaration of interest: In the past 3 years, A.H.Y. received honoraria for speaking from AstraZeneca, Lundbeck, Eli Lilly and Sunovion; honoraria for consulting from Allergan, Livanova and Lundbeck, Sunovion and Janssen; and research grant support from Janssen. In the past 3 years, A.J.C. received honoraria for speaking from AstraZeneca and Lundbeck; honoraria for consulting with Allergan, Janssen, Livanova, Lundbeck and Sandoz; support for conference attendance from Janssen; and research grant support from Lundbeck. B.B. has recently been (soon to be) on the speakers/advisory board for Hexal, Lilly, Lundbeck, Mundipharma, Pfizer, and Servier. No other conflicts of interest.